Relação dos parâmetros de impressão com propriedades mecânicas de peças poliméricas obtidas por impressão 3D pela técnica FDM - Silva, Milena Fontoura da (2022)
Nowadays, the 3D printing technology by FDM (Fused Deposition Modeling) is one of the best-known additive manufacturing processes. In this case, thermoplastic filaments are extruded and deposited in successive layers to build the final object.Since the use of 3D printers becomes increasing, there is a need to know and research how these printed objects respond to external stimuli. Therefore, the objective is to analyze the mechanical behavior of polymers when they are printed using different printing parameters. In the present study, it was choosing the ABS (Acrylonitrile Butadiene Styrene) and PLA (Poly Lactic Acid) materials, due to their use in several segments of the industry, as well as in academic works. The specimens were submitted to tensile strength, Shore hardness and impact toughness tests. The methodology was divided in two parts: the first consisted of printing specimens using FDM technology and varying parameters such as: percentage of filling, printing speed, orientation and layer thickness; in the subsequent step, the mechanical properties of each material were analyzed according to ASTM D 638 (traction), D 2240 (hardness) and D 256 (impact toughness). The results of these tests are that the combination of material PLA and parameters “B” (30% of infill density, 0,3 mm of layer thinkness, infill speed of 40 mm/s and raster angle of 45° -45°), showed the highest tensile strength and hardness on the Shore D scale. In contrast, the ABS material printed with parameters “B” presented the best behavior in the impact test.